Distribution, prevalence and intensity of Anguillicola crassus (Nematoda) infection in Anguilla anguilla in the Republic of Ireland. Issue 4 (13th March 2014) - Becerra‐Jurado, G.; Cruikshanks, R.; O'Leary, C.; Kelly, F.; Poole, R.; Gargan, P.
Abstract This study is the first comprehensive documentation of the geographical range of Anguillicola crassus in its host, the European eel Anguilla anguilla, in the Republic of Ireland. The prevalence and intensity of infections across 234 sites and 93 river basins in Ireland comprising rivers, lakes and transitional waters (estuaries) were analysed. While only 32% of the river basins were affected by this nematode, they correspond to 74% of the total wetted area. Significant differences in infection levels among water body types were found with lakes and transitional waters yielding the highest values, which can be attributed to the proportions of juvenile (total length, LT < 300 mm) A. anguilla caught. There were no significant differences in infection levels between water body types for adult A. anguilla or between sexes for any water body type. Prevalence was significantly lower in juvenile compared with adult A. anguilla captured in rivers and a positive correlation between infection levels and host size‐classes was found. Future efforts should focus on monitoring the spread of A. crassus infections and assessing the swimbladder health of A. anguilla in Ireland.